Supply Chain Planning - Günther, Hans-Otto (Springer, 2017)
Today supply chain management (SCM) is recognized as a powerful competitive weapon. This book addresses decision making activities in SCM at the strategic, tactical and operational decision level. It presents recent research results on collaborative planning in supply chains, demand and inventory management in logistics networks as well as applications in the chemical and automotive industry. The primary focus of this book is on the application of quantitative methods, which also form the basis of commercial advanced planning software systems. Its contributions are written by leading experts from academia and business. The book addresses practitioners as well as academic researchers in supply chain management, logistics and production planning.